Osmanlı Devleti’nde Frengi İle Mücadeleye Adanmış Kısa Bir Ömür: Hüdavendigar Vilayeti Seyyar Frengi Tabibi Nuri Ömer Efendi - Mehmet GÜNEŞ (Gazi Akademik Bakış)
Syphilis which started to be seen as an epidemic especially in Kastamonu province and in Central Black Sea Region, Central Anatolia, Eastern Anatolia and the Balkans beginning from the second half of the 19th century became an important problem for the Ottoman State from the end of the century and maintained its influence also in the 20th century despite the precautions taken. For preventing the disease, numerous precautions were tired to be taken with instructions and regulations puplished in different dates since the 93 War when the disease started to increase again. One of the precautions taken within the scope of these regulations was the establishment of traveling medical committees for the places where there was no hospital and for the ones who were far away and could not go to a hospital. In the field, the traveling physicians were the most active staff of the committee consisting of medical departments and traveling physicians that were divided as affiliated to an traveling medical inspector and according to the sanjaks. Their major duty was to detect patiens and to treat them with the medicine provided by the state by visiting the villages and towns where there was no hospital and following the course of the disease. It was Nuri Ömer Efendi who was one of the traveling physicians operating in various regions of the country in the fight against syphilis in the early 20th century. In this study, it was aimed to provide information related to travel medicine profession with the activities of Nuri Ömer Efendi appointed to the duty of traveling physician of syphilis in Hüdavendigar Province and demonstrating this as the example in the scope of fighting against syphilis in the early 20th century as district of Domaniç in İnegöl being its centre. The major sources of the study were documents in various classifications in the Ottoman Archives of the Prime Ministry.